Risk factor analysis for delayed union after subtrochanteric femur fracture: quality of reduction and valgization are the key to success - Viola Freigang; Franziska Gschrei; Himanshu Bhayana; Paul Schmitz; Johannes Weber; Maximilian Kerschbaum; Michael Nerlich; Florian Baumann (BMC Musculoskeletal Disorders, 2019)
Abstract Background Subtrochanteric femur fractures (SFF) are uncommon, but have a high complication rate concerning non-union and mechanical complications. There is ongoing discussion about risk factors for delayed fracture healing after SFF. The purpose of this study was to evaluate potential risk factors for delayed fracture healing after SFF. Methods This retrospective radio-morphometric case control study compares 61 patients after SFF in two groups (uncomplicated healing within 6 months postoperatively vs. delayed union) concerning radiographical properties. The patients were analyzed concerning the following parameter: Quality of the reduction according to Baumgaertner, CCD-angle, Tip-Apex Distance, leg-length shortening and fracture healing according to the RUSH Score. Results The mean RUSH-Score at 6 months postoperatively was 21.32(±4.57). At that point of time, only 29/61 fractures were radiographically fully consolidated (timely fracture healing) and 32 patients were rated as delayed union. The total revision rate was 9/61 (14.7%), whereof four patients required revision for symptomatic non-union of the SFF. The results of the radio-morphometric measurement showed a significant difference between both groups concerning the degree of reduction measured according to Baumgaertner (p = 0.022). The postoperative ipsilateral CCD-angle was different between the two groups (p = 0.019). After 12 months postoperatively, 48/61 (78.6%) of fractures were rated healed without any further intervention. Conclusions Delayed union after SFF occurs frequently. In our patient population, the quality of reduction and the postoperative CCD-angle were the key factors to avoid delayed union. Level of evidence Level III, Therapeutic study. Trial registration Clinical Trial Registry University of Regensburg Z-2018-1074-1. Registered 04. Aug 2018. https://studienanmeldung.zks-regensburg.de